Variations of the biochemical composition of the alpaca follicular according to the growth status of the ovarian follicle - Pacheco, Joel Iván (2020)
The concentrations of total proteins, glucose, cholesterol, triglycerides, phospholipids, calcium, phosphorus, magnesium, alkaline phosphatase (ALP), aspartate transaminase (AST), alanine transaminase (ALT) and 17-β-estradiol in the follicular fluid were determined in non-pregnant Huacaya alpacas in reproductive age according to the development of the ovarian follicle (size). In total, 60 slaughtered alpacas in the local slaughterhouse were used. Samples of small (<4 mm), medium (5-7 mm) and large (>7 mm) follicles were taken (n = 20 by size). The diameter of the follicles was measured with a vernier and the follicular fluid was aspirated. The samples were analysed in the Biochemistry Laboratory of the Universidad Nacional del Altiplano (Puno, Peru) using colorimetric and spectrophotometric techniques. The concentration results for small, medium and large follicles were: total proteins (5.03, 5.68 and 7.25 g/dl), glucose (45.8, 56.4 and 69.0 mg/dl), cholesterol (3.96, 5.33 and 6.18 mg/dl) , triglycerides (17.91, 14.91 and 12.0 mg/dl), phospholipids (8.99, 6.0 and 6.11 mg/l), calcium (5.76, 8.19 and 9.58 mg/dl), phosphorus (15.69, 10.61 and 10.71 mg/dl), magnesium (2.91, 2.85 and 2.59 mg/dl), ALP (84.6, 75.4 and 75.59 IU/l), AST (238.17, 174.83 and 152.06 IU/l), ALT (24.24, 18.0 and 11.72 IU/l) and 17-β -oestradiol (0.80, 1.91 and 2.39 ng/ml). It is concluded that calcium levels increase, and levels of magnesium and alkaline phosphatase decrease as the oocyte develops, while phosphorus and phospholipid levels decrease from small follicles to medium follicles, then slightly increase in large follicles. Moreover, oestradiol content is directly related to its size.